2011
DOI: 10.33899/rden.2011.9126
|View full text |Cite
|
Sign up to set email alerts
|

Caries Severity of Primary Teeth among Kindergarten Children in Mosul City Using International Caries Detection and Assessment System

Abstract: Aims: To assess the severity of dental caries and its relation to risk factors such as parents' education, income level, demographic variables, dental attendance….etc using the International Caries Detection and Assessment System on the primary teeth of kindergarten children in Mosul City Center. Materials and Methods: The study sample was randomly selected from (8) kindergarten in Mosul City. The sample size was ( 219) child (120 males and 99 females), their ages ranged between (3-6) years. Risk factors consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Mean DMFT, DMFS, dmft and dmfs for females were slightly less than those for males, which is due to the fact that females care with their health and appearance more than males even at a young age. This agreed with other studies, (21)(22)(23)(24) but other studies found the opposite. (15,17) No study is available about the association between the two indices, SiC value and DMFT, in Iraqi children.…”
Section: Discussionsupporting
confidence: 92%
“…Mean DMFT, DMFS, dmft and dmfs for females were slightly less than those for males, which is due to the fact that females care with their health and appearance more than males even at a young age. This agreed with other studies, (21)(22)(23)(24) but other studies found the opposite. (15,17) No study is available about the association between the two indices, SiC value and DMFT, in Iraqi children.…”
Section: Discussionsupporting
confidence: 92%